Using a controlled stimulant to treat cocaine use disorder in the setting of attention deficit/hyperactivity disorder: a case study - Bozman, Mack; Collier, Brent; Malhotra, Aniket; McPherson, Gray; Li, Li (Frontiers in Psychiatry, 2026)
Cocaine Use Disorder (CUD), like all other stimulant use disorders, remains a challenging condition to treat, particularly in the absence of FDA-approved pharmacotherapies. While contingency management (CM) is considered first-line treatment and has demonstrated strong evidence for efficacy, it remains underutilized due to financial, philosophical, and logistical barriers. Off-label use of psychostimulants has emerged as a potential therapeutic strategy, especially in patients with comorbid attention-deficit/hyperactivity disorder (ADHD). We present a case of a middle-aged male with a long-standing history of ADHD and recent onset of CUD, who experienced frequent relapses despite multiple rehabilitation efforts. Following reinstatement of dextroamphetamine-amphetamine salts, the patient demonstrated sustained abstinence from cocaine for six and a half months at the time of this paper—his longest period of remission to date. His sobriety was supported by negative monthly urine drug screens and reduced cravings measured by the Cocaine Craving Scale (CCS). Current evidence supports CM and includes limited but growing support for stimulant substitution therapy. This case highlights the potential role of psychostimulants as a harm-reduction strategy in a carefully selected subset of patients with CUD and co-occurring ADHD. As stimulant use and overdose rates continue to rise, particularly with increasing adulteration by synthetic opioids, further research into effective, individualized treatments for stimulant use disorders, including CUD, is urgently needed.